Catalysing actionable knowledge for youth entrepreneurship: Workshop Highlights - Chavez-Tafur, Jorge (Technical Centre for Agricultural and Rural Cooperation, 2018)
Jorge Chavez-Tafur, Project Coordinator at CTA, shares that the workshop on Catalysing actionable knowledge for youth entrepreneurship went very well and according to him, the best part was the interaction and experience sharing among participants.